CORPORATE IDENTITY DAN PERSONALITY BANK SYARIAH DI SURAT KABAR NASIONAL (Tekstual Analisis Konstruksi Meelalui Publikasi Perusahaan) - Juwono Tri Atmodjo (Jurnal Visi Komunikasi, 2015)
Corporate identity and personality manner that allows employers to formulate and differentiated from other companies (regular bank). Identity and personality can be realized by the company shows the vision and mission of the company, the company philosophy, corporate culture. The study is to assess the identity and personality were constructed through advetorian and Newspaper coverage related to the identity and personality of Islamic banks. Qualitative analysis with textual analysis strategy for observing any publication of the contents of the message, type, appearance, construction built with various combinations of text and images and the meaning behind it seems. Textual research results show that the identity and personality banks Islamic banks, care for the young entrepreneurs of the campus, BNI sharia requires political support, regulatory support, is an ISO 9001: 2008 as the bank has a good quality management. Construction as a bank with a foundation of Sharia as the implementation of Islamic teachings are constructed differently degan regular bank to provide the product name, the expression of interest, section or division, spirit or values and norms derived from the teachings of Islam. Ordinances of service, petuhas services, ornaments firm up souvenirs derived from the values of Islam. Cultural references conveyed Islamic banks oriented to the culture of Islamic countries that appear on the financial system based on gold.